Cytokine Adsorption in Critically Ill COVID-19 Patients, a Case-Control Study. (September 2022) - Abdullayev, Ruslan; Gul, Fethi; Bilgili, Beliz; Seven, Seda; Cinel, Ismail
Aim: New coronavirus disease (COVID-19) has become an international emergency. As many of the intensive care unit (ICU) patients with the disease also present multiple organ failure, blood purification techniques might be a good choice in their treatment. In this study we aimed to investigate the role of cytokine removal in COVID-19 patients managed in ICUs.Methods: For this case-control study we have investigated the role of the cytokine removal by means of two resin membranes (HA330 and Mediasorb) in COVID-19 patients managed in ICUs. Particularly, we investigated the overtime variation in clinical severity scores, laboratory variables, and effects on hospital and ICU stay and mortality.Results: Seventy-two patients have been evaluated, of which half constituted Cytokine Filtration (CF) Group, and other half the Case-Control (CC) Group. Mortality was 55.6% and 50% in CF and CC groups, respectively. In the CF Group, there was decrease in C-reactive protein (CRP) and fibrinogen levels measured at the end of cytokine adsorption; lymphocyte count and ratio were increased, whereas neutrophile ratio was decreased. There were no differences between the groups regarding other laboratory variables, SOFA scores and vasopressor uses.Conclusions: We have demonstrated decrease in CRP, fibrinogen and increase in lymphocyte count in the patients having cytokine adsorption, but there was no clinical reflection of these benefits, and no decrease in mortality as well. Even though there is physio-pathologic rationale to use cytokine adsorption techniques for immunomodulation in critically ill COVID-19 patients, it is early to make strong suggestions about their benefits.